(untitled) (Research, Society and Development, 2020)
The purpose of this article was to prove that the MESMIS method (Marco de Evaluación de Sistemas de Manejo Incorporando Indicadores de Sustentabilidad) can be used to measure the sustainability of rural environments in different realities. For this, a systematic literature review on the method was carried out in six renowned scientific article bases, where searches were made from 1999 to 2019 and the articles found were divided according to the year of publication, evaluated productive activity, region geographic area where the research was carried out, among other classifications. At the end it was possible to verify that MESMIS use has been increasing in the last years, being that the published researches that used the method are mainly on the measurement of the sustainability of agriculture and animal production activities, carried out mostly in the Americas and Europe , but also with use in other continents, thus proving the method can be used to measure sustainability in different scenarios.